PKM DESAIN DAN PERANCANGAN PRODUK TEXTILE CIRCUIT RAGAM MOTIF: PKM DESAIN DAN PERANCANGAN PRODUK TEXTILE CIRCUIT RAGAM MOTIF - Titin wahyuni; andi Yusri; Ridwang Ridwang; Lukman Anas (PPM LP2M UIN Alauddin Makassar, 2022)
The Maudu Lompoa celebration is held once a year by the Cikoang community. During the Maudu Lompoa celebration in Indonesian (Maulid Great Prophet Muhammad SAW). In the village of Cikoang, Mangara Bombang District, Takalar district, many outsiders come to visit this village. The opportunity is to be able to promote merchandise or handicrafts when there is a lot of crowd. Moreover, at this time, the condition of the Covid-19 pandemic has paralyzed all activities, which will result in family income. The fact as stated above interested our to empower the community regarding the manufacture of textile circuit products that can be marketed on the Maudu Lompoa holiday and become a source of income during the COVID-19 Pandemic Period, where people who came from outside came to this village while promoting goods , use of technology online marketing. Solutions Problems that are generated according to the planned activities are as follows: 1) Increased knowledge of teenagers dropping out of school in taking advantage of opportunities and increasing income of the family through making Textile Circuit 2) Increased knowledge of out of school youth in making Motif Designs and Embroidering Techniques Textile Circuit 3) Increased knowledge of school dropouts in the use of 3D printing technology makes it possible to order online and according to the wishes of consumers during the Covid-19 pandemic and the New Normal Era 4) Skilled teenagers who have dropped out of school in conducting E-Marketing activities. Expected results Activity 1. Introduction and opening of the activity, the first meeting is held inside with the opening of the activity, introductions between the organizing committee, field assistants and partners (trainees) and continued with the presentation of training material Activity 2. Giving material to the group of out-of-school youth (partners) who are trained, regarding (1) making a series of textile circuits ; 2) design Motive and Technique Embroidery textuile Circuit; 3) making and Design Accessories Clothing 3D based printing according ; 4) making Application marketing Product based E-learning